Description of Chemosensory Genes in Unexplored Tissues of the Moth Spodoptera littoralis - Koutroumpa, Fotini A.; Monsempes, Christelle; François, Marie-Christine; Severac, Dany; Montagné, Nicolas; Meslin, Camille; Jacquin-Joly, Emmanuelle (Frontiers in Ecology and Evolution, 2021)
Illumina-based transcriptome sequencing of chemosensory organs has become a standard in deciphering the molecular bases of chemical senses in insects, especially in non-model species. A plethora of antennal transcriptomes is now available in the literature, describing large sets of chemosensory receptors and binding proteins in a diversity of species. However, little is still known on other organs such as mouthparts, legs and ovipositors, which are also known to carry chemosensory sensilla. This is the case of the noctuid Spodoptera littoralis, which has been established as a model insect species in molecular chemical ecology thanks to the description of many—but not all—chemosensory genes. To fulfill this gap, we present here an unprecedented transcriptomic survey of chemosensory tissues in this species. RNAseq from male and female proboscis, labial palps, legs and female ovipositors allowed us to annotate 115 putative chemosensory gene transcripts, including 30 novel genes in this species. Especially, we doubled the number of candidate gustatory receptor transcripts described in this species. We also evidenced ectopic expression of many chemosensory genes. Remarkably, one third of the odorant receptors were found to be expressed in the proboscis. With a total of 196 non-overlapping chemosensory genes annotated, the S. littoralis repertoire is one of the most complete in Lepidoptera. We further evaluated the expression of transcripts between males and females, pinpointing sex-specific transcripts. We identified five female-specific transcripts, including one odorant receptor, one gustatory receptor, one ionotropic receptor and one odorant-binding protein, and one male-specific gustatory receptor. Such sex-biased expression suggests that these transcripts participate in sex-specific behaviors, such as host choice for oviposition in females and/or mating partner recognition in both sexes.